Anterior cruciate ligament injury prevention in female adolescents - Otsuki, R.; Fukubayashi, T. (Sports injuries and prevention, 2015)
Anterior cruciate ligament (ACL) injuries are frequently seen in female adolescents. Lower extremity mechanics change as female adolescents mature. The biomechanical changes associated with female pubertal growth could be contributing factors to the increased occurrence of ACL injury after puberty. Several studies have demonstrated that injury prevention training was effective in improving lower extremity kinematics. In addition, some intervention studies have reported that implementing injury prevention training can reduce the incidence of ACL injury in female adolescents. Intervening at a younger age and limiting the changes in mechanics that occur during puberty might be important in the prevention of ACL injuries